Home Sweet Home: Yeasts Living in Substrates Related with Melipona scutellaris in the Brazilian Atlantic Forest - Barbosa, Renan do Nascimento; Bezerra, Jadson D. P.; Moura, Joana C. de; Santos, José Ewerton F. dos; Oliveira Junior, Isaias; Souza-Motta, Cristina M. de; Oliveira, Neiva T. de (Sociobiology, 2024)
The interaction between stingless bees and fungi has garnered recent interest due to potential mutual benefits. In Brazil, Melipona scutellaris stands out ecologically and economically. We investigated its microbiota, focusing on yeast species in pot-honey, pot-pollen, and nest surfaces. Samples from the Atlantic Forest (Pernambuco state, Brazil) were analyzed through morphological and physiological methods and D1/D2 LSU rDNA sequence analysis. We identified 20 yeast species, comprising 15 ascomycetes and five basidiomycetes, representing 11 and five genera, respectively. All yeast species, except Blastobotrys meliponae, were reported for the first time in association with M. scutellaris. Honey exhibited the highest species richness. In this study, the species Blastobotrys meliponae, Meyerozyma caribbica, Wickerhamomyces anomalus, and Moniliella carnis were exclusively isolated from honey. The understanding of the ecological association between stingless bees and yeasts, as revealed in our research, can significantly aid in insect conservation programs. We present the first report of yeasts associated with M. scutellaris substrates living in the Brazilian Atlantic Forest.